Monitoring kualitas tanah lahan pertanian Desa Sidorejo menggunakan sensor pH tanah dan Internet of Things - Gatot Santoso; Slamet Hani; Uhing Dwi Putra (Jurnal Nusantara Mengabdi, 2022)
Purpose: Assisting farmers in monitoring remotely the quality of agricultural land for rice crops in Sidorejo Village, Bantul Regency, Yogyakarta. As well as farmers and the agriculture office can determine the composition of the fertilizer given to suit their rice plants. Method: The installed soil pH sensor will read the soil pH value for rice plants in the form of voltage, then the data from the voltage is processed by Arduino Nano and sent to the internet cloud using the SIM800L module. Result: With a soil pH value of 2.79, it will produce 800 kg of grain from an area of ??600 m2, while a soil pH value of 3.41 will also produce 500-600 kg of grain from an area of ??350 m2. Conclusion: The application of a soil quality monitoring system for rice plants in Siderejo Village, Bantul Regency, Yogyakarta has been successfully implemented with an average control speed of 5,11-6,8 second, and the data can be accessed by farmers using mobile phones.